2022
DOI: 10.1007/s12325-022-02085-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Sipuleucel-T on Overall Survival in Men with Advanced Prostate Cancer Treated with Androgen Receptor-Targeting Agents

Abstract: Introduction The treatment landscape for metastatic castration-resistant prostate cancer (mCRPC) continues to evolve. Sipuleucel-T was the first immunotherapy approved by the US Food and Drug Administration (FDA) to treat asymptomatic or minimally symptomatic mCRPC. The androgen receptor-targeting agents (ARTAs) abiraterone acetate and enzalutamide were initially approved to treat mCRPC. Looking at chemotherapy-naïve men with mCRPC, we compared survival outcomes between the sipuleucel-T + ARTA coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…This open-label phase I trial demonstrated a good safety and biological activity profile for Rheumavax as indicated by an increased ratio of Treg to T effector (Teff) cells and decreases in disease activity score in 28 joints (DAS28) within 1 month in Rheumavax-treated patients ( Table 1 ). Again, although autologous cell therapies have been commercially available for almost a decade ( 43 ), to date, they have not been proven to be economically successful due to the extremely high cost of generating these patient-specific cells.…”
Section: Antigen-specific and Immunomodulatory Therapies In Ra And An...mentioning
confidence: 99%
“…This open-label phase I trial demonstrated a good safety and biological activity profile for Rheumavax as indicated by an increased ratio of Treg to T effector (Teff) cells and decreases in disease activity score in 28 joints (DAS28) within 1 month in Rheumavax-treated patients ( Table 1 ). Again, although autologous cell therapies have been commercially available for almost a decade ( 43 ), to date, they have not been proven to be economically successful due to the extremely high cost of generating these patient-specific cells.…”
Section: Antigen-specific and Immunomodulatory Therapies In Ra And An...mentioning
confidence: 99%
“…Hinsichtlich der Sicherheit waren die häufigsten unerwünschten Ereignisse in der Sipuleucel-T-Gruppe Kopfschmerzen und Fieber [134]. Derzeit laufen Studien zur Kombination dieses Impfstoffs mit den Zielwirkstoffen AR [136], Atezolizumab [137] oder Radio-223 [138] bei Patienten mit mCRPC. Er ist der einzige von der FDA zugelassene Impfstoff gegen PCa.…”
Section: Impfstoffbasierte Immuntherapieunclassified
“…DC vaccines have shown OS benefits in solid tumors such as prostate cancer ( 152 ), melanoma ( 153 ), glioblastoma ( 154 ), and ovarian cancer ( 155 ). The studies showed that inactivated tumor cells ( 156 ), tumor lysates ( 153 ), tumor vesicles ( 157 ), synthetic tumor peptides ( 158 ), or synthetic tumor antigen mRNA ( 159 ) all can be used as DC vaccine–loaded antigens.…”
Section: Dcs-based Immunotherapymentioning
confidence: 99%